Brics as a Dynamic and in Process Phenomenon of Global Planning: An Analysis Based on the 2009-2020 Annual Summit Declarations - Daldegan, William; Carvalho, Carlos Eduardo [UNESP] (Pontificia Universidade Catolica de Minas Gerais, 2022)
Brazil, Russia, India, China, and South Africa are very heterogeneous countries and the BRICS is a very original arrangement. This paper asserts that the BRICS is a dynamic and in process phenomenon: dynamic because it is developed according to the member's perceptions about world scenario, without establishing limitations on strategies and initiatives of each member country; in process because it is developed through specific processes, in which members do not point any destination or institutionalization to be achieved. At the annual summit meetings held regularly since 2009, the BRICS issues a Declaration. The most prominent topics on the international framework are punctuated and criticized, with generic proposals to handle or to solve them. The declarations do not show any progressive stages on approaching these topics, neither consolidation of commitments among the members on them. Such documents represent the main primary source for the characterization of the group and its behavior. The innovation of this paper is to deepen the use of primary sources to move forward in the effort for the BRICS conceptualization and to analyze its performance throughout the years. The documentary analysis of Summit Declarations is developed by using two text analysis software packages, AntConc and VOSviewer.
Brics como Fenómeno Dinámico y en Proceso de la Coyuntura Global: un análisis basado en las Declaraciones anuales de la Cumbre 2009-2020
Brics como Fenômeno Dinâmico e Processual da Conjuntura Global: uma análise baseada nas Declarações das Cúpulas anuais de 2009-2020
Keywords: BRICS Countries; BRICS Summit Declarations; Documentary Analysis; Documentary Sources; Governance Instruments